A cyanine dye supramolecular FRET switch driven by G-quadruplex to monitor mitophagy. (August 2021) - Guo, Xiaomeng; Yang, Dawei; Sun, Ranran; Li, Qian; Du, Hongyan; Tang, Yalin; Sun, Hongxia
Abstract: Mitochondrial autophagy (mitophagy) is critical to the quality and quantity control of mitochondria. Real-time monitoring of the occurrence of mitophagy is necessary for understanding mitochondrial metabolism and screening mitophagy-related therapeutic drugs. Here, we report a new type of fluorescence resonance energy transfer (FRET) switch constructed by the mixed assembly of two cyanine dyes. The FRET switch exhibits a highly selective fluorescence response to the G-quadruplex structure, and its fluorescence intensity decreases or increases correspondingly with the binding and separation of G-quadruplexes. This property enables the switch to track the progression and termination of mitophagy by identifying the G-quadruplex structures that enter the lysosome during autophagy. This work not only provides a new strategy for constructing non-covalent FRET probes, but also offers a reliable tool for tracking mitophagy. Highlights: A new type of mixed aggregate was constructed by assembling two cyanine dyes. This mixed aggregate has the unique property of emitting FRET fluorescence. The mixed aggregate can be regarded as a FRET switch driven by G-quadruplex. The FRET switch can be applied to track the occurrence and termination of autophagy.